1990
DOI: 10.1259/0007-1285-63-756-975
|View full text |Cite
|
Sign up to set email alerts
|

Paraganglioma of the duodenum: a case report with radiological findings and literature review

Abstract: Paraganglioma of the gastrointestinal tract is an uncommon, usually benign neoplasm. It usually occurs in the second section of the duodenum. A review of the literature reveals 73 reported cases. We studied a case of paraganglioma by hypotonic duodenography (HDG), computed tomography (CT), angiography and histological examination. The rare occurrence of this neoplasm and the first comparative study using HDG, CT and angiography justify this case report. A 65-year-old Japanese woma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Imai et al 3 reported that the incidence of ulceration in these lesions was approximately 40% in the patients previously reported in other countries. Smithline et al 6 reported that ultrasonic endoscopy showed at heterogeneous solid echo continuing from the submucosal layer, and indicated that endoscopic ultrasonography was useful for preoperative differential diagnosis.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Imai et al 3 reported that the incidence of ulceration in these lesions was approximately 40% in the patients previously reported in other countries. Smithline et al 6 reported that ultrasonic endoscopy showed at heterogeneous solid echo continuing from the submucosal layer, and indicated that endoscopic ultrasonography was useful for preoperative differential diagnosis.…”
Section: Discussionmentioning
confidence: 84%
“…The incidence was slightly higher in males. Five patients had digestive tract hemorrhage related to tumor ulceration, while 5 patients had 3 summarized patients previously reported in countries other than Japan, and reported that the incidences of digestive tract hemorrhage and abdominal pain were 47% and 33%, respectively. In the 25 patients previously reported in Japan, the tumor size ranged from 10 mm to 65mm, with a mean of 28.9mm.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mean age of patients in a case series from Japan was 54 years, with a slight male predominance. 31,32 Gastrointestinal bleeding and abdominal pain are common presenting symptoms. 32 Because the tumor is submucosal, mucosal biopsies are often negative and endoscopic or surgical resection is needed for the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Gastrointestinal bleeding and abdominal pain are common presenting symptoms. 32 Because the tumor is submucosal, mucosal biopsies are often negative and endoscopic or surgical resection is needed for the diagnosis. EUS may be useful in confirming the submucosal location of these tumors.…”
Section: Discussionmentioning
confidence: 99%